Climate change and infectious diseases in Australia's Torres Strait Islands. (1st February 2021) - Hall, Nina L.; Barnes, Samuel; Canuto, Condy; Nona, Francis; Redmond, Andrew M.
Abstract: Objective : This research seeks to identify climate‐sensitive infectious diseases of concern with a present and future likelihood of increased occurrence in the geographically vulnerable Torres Strait Islands, Australia. The objective is to contribute evidence to the need for adequate climate change responses. Methods : Case data of infectious diseases with proven, potential and speculative climate sensitivity were compiled. Results : Five climate‐sensitive diseases in the Torres Strait and Cape York region were identified as of concern: tuberculosis, dengue, Ross River virus, melioidosis and nontuberculous mycobacterial infection. The region constitutes 0.52% of Queensland's population but has a disproportionately high proportion of the state's cases: 20.4% of melioidosis, 2.4% of tuberculosis and 2.1% of dengue. Conclusions : The Indigenous Torres Strait Islander peoples intend to remain living on their traditional country long‐term, yet climate change brings risks of both direct and indirect human health impacts. Implications for public health : Climate‐sensitive infections pose a disproportionate burden and ongoing risk to Torres Strait Islander peoples. Addressing the causes of climate change is the responsibility of various agencies in parallel with direct action to minimise or prevent infections. All efforts should privilege Torres Strait Islander peoples' voices to self‐determine response actions.